The Role of Digital Transformation in Enhancing Governance and Social Development in Morocco (The International Journal for Scientific Research, 2025)
Objectives: This article aims to clarify the role of digital transformation in Morocco and its relationship with economic and social development by adopting digital solutions in various fields such as public procurement, financial and tax management. It also seeks to define the concept of digital governance by achieving social and territorial justice, reducing disparities in basic services such as education and healthcare, and ensuring their fair and equitable access to all regions.Methodology: This study adopted the descriptive-analytical approach, which is the most suitable method for analysing the phenomenon of digital transformation in Morocco. It allows for describing the current reality and analysing its effects and effectiveness in improving the quality of public facilities and services.Results: Through the process of digital transformation, public expenditures have been rationalized, and the stability and sustainability of public finances have been enhanced. It has also contributed to improving the quality of educational and healthcare services, reducing territorial disparities, thereby strengthening social and territorial justice. Additionally, the efficiency of human resources has been improved, and the scope of basic services has been expanded to include all segments of society.Recommendations: To ensure the continued success of digital transformation, it is recommended to strengthen digital infrastructure across the Kingdom, especially in remote areas. Efforts should also be made to train human resources to ensure the optimal use of technology. Furthermore, transparency and governance in the application of digital solutions should be enhanced to ensure that the desired benefits are achieved fairly.Conclusion: In summary, digital transformation in Morocco constitutes a fundamental strategy for achieving sustainable development and promoting social and territorial justice. By improving the efficiency of public services and expanding their reach, digital transformation can be a powerful tool for achieving economic and social progress, while ensuring equitable and effective access to basic services for all citizens.
Keywords: Digital Transformation; Economic Development; Social and Territorial Justice; Governance; Healthcare; Education; Public Procurement; Financial and Tax Management